"They treated me like crap and I know it was because I was Native": The healthcare experiences of Aboriginal peoples living in Vancouver's inner city. (April 2017) - Goodman, Ashley; Fleming, Kim; Markwick, Nicole; Morrison, Tracey; Lagimodiere, Louise; Kerr, Thomas
Abstract: There is growing evidence that Aboriginal peoples often experience healthcare inequalities due to racism. However, research exploring the healthcare experiences of Aboriginal peoples who use illicit substances is limited, and research rarely accounts for how multiple accounts of stigma intersect and contribute to the experiences of marginalized populations. Our research aimed to explore the healthcare experiences of Aboriginal peoples who use illicit drugs and or illicit alcohol (APWUID/A) living in Vancouver's inner city. Using Indigenous methodologies, a community research team comprised of APWUID/A led the study design, data collection and analysis. Peer-facilitated talking circles explored community members' experiences accessing healthcare services and patient-provider encounters. Using an intersectionality framework, our research demonstrated how healthcare inequalities among Aboriginal peoples are perpetuated by systemic racism and discrimination. Stigmatizing racial stereotypes were perceived to negatively influence individual attitudes and clinical practice. Participants' experiences of medical dismissal often resulted in disengagement from care or delay in care. The findings suggest healthcare providers must understand the structural and historical forces that influence racial disparities in healthcare and personal attitudes in clinical practice. Adequate clinical protocols for pain management within the context of illicit substance use are urgently needed. The valuation of Aboriginal peoples and cultures within healthcare is paramount to addressing the health gap between Aboriginal and non-Aboriginal Canadians. Highlights: Indigenous-led research explored factors shaping peers' healthcare experiences. Racial stereotypes about Aboriginal peoples influence clinical practice. Adverse care experiences often resulted in disengagement from care or delay in care. Clinical protocols for pain management among substance-using patients are needed. Clinicians must recognize the historical context of Aboriginal health inequities.